(untitled) (Architecture Image Studies, 2026)
Globalization refers to an accelerated process of interaction and interconnection among societies and states across political, economic, and cultural domains, driven by technological advancement, the communications revolution, and market liberalization. In the twenty-first century, globalization has contributed to reshaping the structure of the international system by relatively diminishing the traditional role of the nation-state and enhancing the influence of non-state actors, such as multinational corporations and international organizations. This transformation has had profound implications for political decision-making processes and national sovereignty. On the cultural level, globalization has intensified cultural exchange among peoples and facilitated the spread of shared global cultural patterns. At the same time, it has raised growing concerns about the erosion of national identities and the threat to local cultural specificities. Moreover, globalization has generated a complex interaction between local and global cultures, manifested in simultaneous processes of cultural adaptation and resistance. Therefore, globalization represents a multidimensional phenomenon with both positive and negative consequences, making its study essential for understanding political and cultural transformations in the contemporary world.